Increased cellular levels of spermidine or spermine are required for optimal DNA synthesis in lymphocytes activated by concanavalin A. - Fillingame, R H (1975)
There are large increases in cellular levels of the polyamines spermidine and spermine in lymphocytes induced to transform by concanavalin A. The anti-leukemic agent methylglyoxal bis(guanylhydrazone) (MGBG) blocks synthesis of these polyamines by inhibiting S-adenosylmethionine decarboxylase. Previous results showed that when cells are activated in the presence of MGBG the synthesis and processing of RNA, as well as protein synthesis, proceed as in the absence of the drug. In contrast, the incorporation of [methyl-3H]thymidine into DNA and the rate of entry of the cells into mitosis are inhibited by 60% in the presence of MGBG. Several experiments suggest that MGBG inhibits cell proliferation by directly blocking polyamine synthesis and not by an unrelated pharmacological effect: (1) the inhibitory action of MGBG is reversed by exogenously added spermidine or spermine; (2) inhibition of DNA synthesis by MGBG shows the same dose-response curve as does inhibition of spermidine and spermine synthesis; and (3) if MGBG is added to cells which have been allowed to accumulate their maximum complement of polyamines, there is no inhibition of thymidine incorporation. MGBG-treated and control cultures initiate DNA synthesis at the same time and show the same percentage of labeled cells by autoradiography. Therefore, it appears that in the absence of increased cellular levels of polyamines, lymphocytes progress normally from G0 through G1 and into S-phase. Furthermore, these experiments suggest that the increased levels of spermidine and spermine generally seen in rapidly proliferating eukaryotic systems are necessary for enhanced rates of DNA replication.